The Effectiveness of Using Quizizz Application in Learning English at Online Learning at the Eleventh Grade of SMA N 1 Padang Gelugur - Putri, Rezkia Sarah; Roza, Veni; Reflinda, Reflinda; Dewi, Merry Prima (International Journal of Education, Culture, and Society, 2024)
This research was done because the researcher found several problems in students’ ability in learning English at SMAN 1 Padang Gelugur. The phenomenon was the teacher had used Quizizz application in learning English but the students’ ability in learning English was still variaties: the ability in Learning English of some of students was high and of some others was not, although the theories stated that using Quizizz application can help students to solve their problems in learning English. Hence, this research was done to know whether the Quizizz application is effective or not in teaching learning English for eleventh grade students at SMAN 1 Padang Gelugur. The design of this research was a descriptive quantitative. The data was gotten through documentation of scores from students after using Quiziz application in learning English. The total of sample was 32 students of XI.1 – XI.4 classes. The researcher used simple random sampling in the determining the sample because the population was more than 100. To analyze the data collected, the researcher used rating scale table to see the level of effectiveness. The result is that Quizizz application is not effective in learning English. The result showed that the mean score of the students’ writing ability gotten was 53 %. This score lies in range 36% - 53%. It means, the Quizizz application is not effective in learning English in the eleventh grade of SMAN 1 Padang gelugur.